2007
DOI: 10.1016/j.jcsr.2006.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Semi-analytical buckling strength analysis of plates with arbitrary stiffener arrangements

Abstract: Buckling of plates with arbitrarily oriented, sniped stiffeners is studied. The main objective is to present and validate an approximate, semianalytical computational model for such plates subjected to in-plane loading. Estimation of the buckling strength is made using the von Mises' yield criterion for the membrane stress as the strength limit. The formulations derived are implemented in a Fortran computer code, and numerical results are obtained for a variety of plate and stiffener geometries. The model may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…It is found that z c = 0 is an acceptable value for eccentric stiffeners in many practical cases as well. In practical design work, a z c -value calculated with a b e of about b e = 20t has been suggested [8,15].…”
Section: Elastic Buckling Stress Limit (Esl)mentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that z c = 0 is an acceptable value for eccentric stiffeners in many practical cases as well. In practical design work, a z c -value calculated with a b e of about b e = 20t has been suggested [8,15].…”
Section: Elastic Buckling Stress Limit (Esl)mentioning
confidence: 99%
“…Similarly, contributions have to be added for any rotational or translational restraints in the interior of the plate. For additional details, see Brubak et al [8,15]. …”
Section: Elastic Buckling Stress Limit (Esl)mentioning
confidence: 99%
See 1 more Smart Citation
“…Three edges are supported (continuously) in the out-ofplane direction, and the last edge is either completely free or provided with an edge stiffener. A supported edge boundary may be simply supported, or it may be clamped or partially restrained by adding rotational spring restraints along the edges, or parts of the edges, in the same manner as described in Brubak and Hellesland [9].…”
Section: Problem Formulation and Plate Definitionmentioning
confidence: 99%
“…(5), (7) and (10)), but with only one term in each direction, are used in Bažant and Cedolin [16] to study simply supported, unstiffened plates. By including more terms in the displacement fields in each direction, it is also possible to model stiffened plates in the same manner as in Brubak et al [9,14,17]. For the displacement fields representing a plate with a free edge (Eqs.…”
Section: Present Displacement Fieldmentioning
confidence: 99%